Point-of-Care Haematology Analyser Quality Assurance Programme: a rural nursing perspective - Geoffrey Herd; Katharina Blattner; Catherine Beazley (CSIRO Publishing, 2021)
ABSTRACT BACKGROUND AND CONTEXTRural health services without an onsite laboratory lack timely access to haematology results. Set in New Zealand's far north, this paper provides a rural nursing perspective on how a health service remote from a laboratory introduced a haematology analyser suitable for point-of-care use and established the associated quality assurance programme. ASSESSMENT OF PROBLEMFive broad areas were identified that could impact on successful implementation of the haematology analyser: quality control, staff training, physical resources, costs, and human resource requirements. RESULTSQuality control testing, staff training and operating the haematology analyser was more time intensive than anticipated. Finding adequate physical space for placement and operation of the analyser was challenging and costs per patient tests were higher than predicted due to low volumes of testing. STRATEGIES FOR IMPROVEMENTThrough a collaborative team approach, a modified quality assurance programme was agreed on with the supplier and regional point-of-care testing co-ordinator, resulting in a reduced cost per test. The supplier provided dedicated hours of staff training. Allocated time was assigned to run point-of-care testing quality assurance. LESSONSHaving access to laboratory tests can reduce inequalities for rural patients, but natural enthusiasm to introduce new point-of-care technologies and devices needs to be tempered by a thorough consideration of the realities on the ground. Quality assurance programmes need to fit the locality while being overseen and supported by laboratory staff knowledgeable in point-of-care testing requirements. Associated costs need to be sustainable in both human and physical resources.